2017
DOI: 10.1002/anie.201700357
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Nanoscale Thermostability of Cell Membranes with Single Gold–Diamond Nanohybrids

Abstract: Much of the current understanding of thermal effects in biological systems is based on macroscopic measurements. There is little knowledge about the local thermostability or heat tolerance of subcellular components at the nanoscale. Herein, we show that gold nanorod-fluorescent nanodiamond (GNR-FND) hybrids are useful as a combined nanoheater/nanothermometer in living cells. With the use of a 594 nm laser for both heating and probing, we measure the temperature changes by recording the spectral shifts of the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 38 publications
(51 reference statements)
1
81
0
Order By: Relevance
“…A two-in-one nanodevice which provides heating and temperature sensing at the same time and the same spot is a straightforward strategy for measuring intracellular thermal conductivity locally. Tsai et al has reported the use of fluorescent nanodiamond (FND) and gold nanorods (GNRs) 26,27 . FNDs containing negatively charged nitrogen vacancy centers (NVCs) are known as a fluorescent nanomaterial with exceptional photostability, showing neither photobleaching nor photoblinking 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-in-one nanodevice which provides heating and temperature sensing at the same time and the same spot is a straightforward strategy for measuring intracellular thermal conductivity locally. Tsai et al has reported the use of fluorescent nanodiamond (FND) and gold nanorods (GNRs) 26,27 . FNDs containing negatively charged nitrogen vacancy centers (NVCs) are known as a fluorescent nanomaterial with exceptional photostability, showing neither photobleaching nor photoblinking 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Since NVCs are deeply embedded inside a diamond crystal with high thermal conductivity (larger than 50 Wm -1 K -1 ) 32 , its thermosensing ability is little influenced by environmental factors 33 . Physically bound FND and GNR serve as a nanoheater and nanothermometer at the same time 26,27 because GNRs release heat when exposed to light via strong surface plasmon resonance 34,35 . However, the stoichiometry of FND/GNR ratio is difficult to control and GNR can be deformed by heating, which makes quantitative and reproducible experiments difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In this context one may not be interested in the method's sensitivity only, but also in the accessible bandwidth the individual sensing strategy provides. The zero phonon line energy and the Debye-Waller-factor (DWF) of NV are temperature dependent and allow an all optical approach [11,12]. Thus, measuring both quantities is very easy to implement, and show a comparable sensitivity to microwave assisted techniques in case of DWF and NVs in NDs.…”
Section: Resultsmentioning
confidence: 99%
“…One representative of such quantum sensors, is the negatively charged nitrogen-vacancy center (NV) in diamond. Several applications as a magnetic [1] and electric field [2], pressure [3] and temperature [4][5][6][7][8][9][10][11][12] probe have been demonstrated. In addition, one can also extract chemical information about samples by nuclear magnetic resonance with ∼Hz spectral and nanometer-scale spatial resolution [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these applications concern precise temperature sensors around room temperature in living organisms based on the thermal dependence of their photoluminescence spectra [8,10]. NV centers however suffer of low intensity of its zero-phonon line (ZPL line) notably around room temperature, which complicates line position measurements [8,[10][11][12][13][14][15][16][17]. ZPL line position of NV centres is also dependent on other factors such as strain and impurities.…”
Section: Introductionmentioning
confidence: 99%